PENGARUH BODY IMAGE TERHADAP KEPERCAYAAN DIRI SISWA - Muyana, Siti; Salamah, Dara Gati Mustikaning; Hestiningrum, Erni; Barida, Muya (Universitas Muria Kudus, 2022)
Everyone has their own standard of physical form. But in reality, not everyone has a physique that matches the standards he has made. This triggers many people who are less confident with their physical form. This condition makes researchers carry out research that intends to see the effect of body image on self-confidence. This research uses correlational quantitative research with student subjects. This research instrument uses a body image scale and a self-confidence scale. Validity testing uses expert tests and trials, while reliability uses Cronbach's Alpha. This research data analysis technique uses the Linear Regression formula. The results of the research show that there is an effect of body image on students' self-confidence. The magnitude of the influence of Body Image on self-confidence is 35.8%.